CoMo-BTNT anode, preparation method and application thereof
By filling nanoparticles in the TNA channel and depositing Co-Mo oxide layer, CoMo-BTNT anode was prepared, which solved the problem of restricted charge transfer of anatase TNA, improved the conductivity and electrocatalytic performance of the anode, and achieved the correctness of the Efficient degradation of tetracycline wastewater.
Patent Information
- Application Number
- CN202411780422.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-05
AI Technical Summary
When anatase TNA is used in anode materials, the charge transfer is limited, resulting in poor electrooxidation capacity and poor ability to degrade persistent organic pollutants.
Nanoparticles were uniformly filled in the TNA channel, and the Co-Mo oxide layer was deposited by DC electrodeposition to form CoMo-TNA. Then, CoMo-TNA was used as the cathode and Pt sheet was used as the anode to perform cathode reduction, and CoMo-BTNT anode was prepared.
The conductivity and electrocatalytic properties of the anode were significantly improved, and an effective electrically assisted activation PMS degradation system was constructed, which improved the treatment capacity of tetracycline wastewater.
Smart Images

Figure CN119433653A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a CoMo-BTNT anode, a preparation method and application thereof. Background Art
[0002] Tetracycline antibiotics (TCs) are one of the most widely used antibiotics in the world, mainly used in clinical medicine, livestock and poultry farming, aquaculture and other industries. Since these compounds are not easily absorbed by organisms, difficult to degrade in the environment, and difficult to completely remove in conventional sewage treatment systems, they pose a serious threat to ecosystems and human health. Therefore, it is of great significance to develop efficient tetracycline deep purification technology.
[0003] Based on sulfate free radical (SO4 ·- Advanced oxidation technology (AOT) is considered an attractive method for degrading organic pollutants due to its higher redox potential, longer half-life, milder pH conditions and higher selectivity. In this case, the selection of anode materials is crucial.
[0004] Vertically oriented blue-black TiO2 nanotube arrays (TNA) are widely used as host catalysts or interlayers in (photo)electrochemical AOPs to remove organic pollutants due to their tubular structure with high aspect ratio, large specific surface area and more active sites. However, anatase TNA usually exhibits n-type semiconductor properties, and charge transport is limited, resulting in unsatisfactory electrooxidation ability and poor ability to degrade persistent organic pollutants, thus limiting its application in anode materials. Summary of the invention
[0005] In order to solve this problem, the inventors found that uniformly filling nanoparticles in the TNA channel is an effective method, which can significantly improve the efficiency of directional electron transfer and surface activity. Based on this, the present invention has developed a Co / Mo-BTNT anode with multi-metal synergistic catalysis. Specifically, the present invention uses TNA as a base layer, and deposits an active CoMo oxide layer thereon, which has good conductivity and electrocatalytic performance, improves the conductivity of the anode, and constructs an effective electric-assisted activation PMS degradation tetracycline system, providing a new solution for the treatment of tetracycline wastewater.
[0006] The embodiments of the present invention are achieved through the following technical solutions:
[0007] First, the present invention provides a method for preparing a CoMo-BTNT anode, comprising the following steps:
[0008] (1) preparing a Ti substrate;
[0009] (2) Preparation of titanium dioxide nanotube arrays (TNA) using Ti substrate;
[0010] (3) depositing a Co-Mo oxide layer deposition liquid onto the TNA surface by a direct current electrodeposition method, and then performing an annealing heat treatment to prepare CoMo-TNA;
[0011] (4) CoMo-BTNT anode was prepared using CoMo-TNA as cathode and Pt sheet as anode; BTNT represents blue titanium dioxide nanotube array.
[0012] More specifically, when preparing the Ti substrate in step (1), the following steps are included: first, the titanium foil is polished with sandpaper of 600, 800, 1500 and 2000 meshes in sequence to remove the oxide layer on the surface of the titanium foil, and then the titanium foil is cut into titanium sheets of the required size. Thereafter, the titanium sheet is cleaned in an ultrasonic bath for 30-60 minutes using acetone, ethanol and ultrapure water in sequence, and the cleaned titanium sheet is immersed in an oxalic acid solution with a concentration of 10-20%, and heated in a water bath at a constant temperature of 90-100° C. for 1.5-2.5 hours. When the surface of the titanium sheet becomes pockmarked, the treatment is stopped, and the sheet is cleaned to obtain the Ti substrate.
[0013] When preparing TNA in step (2), the following steps are included: using the Ti substrate as the anode and the Pt sheet as the cathode, and performing the first anodization in an electrolyte containing fluoride ions for a period of time; then continuing to perform the second anodization in the electrolyte containing fluoride ions for a period of time, and finally flushing the electrolyte remaining on the surface of the Ti substrate to obtain a titanium dioxide nanotube array; more specifically, using the Ti substrate as the anode and the Pt sheet as the cathode in a mixed solution of 0.25% by mass NH4F and 2% by mass H2O ethylene glycol, anodizing at 60V for 1-2h; then continuing to perform anodization in a mixed solution of 0.1% by mass NH4F and 1% by mass H2O ethylene glycol for 3-5h. After the oxidation is completed, the electrolyte remaining on the surface of the Ti substrate is flushed with ultrapure water to obtain a TNA substrate.
[0014] The first step of anodization of the present invention is to prepare a titanium dioxide nanotube array with vertical surface growth on a Ti substrate, and then use deionized water or acid to wash away the prepared titanium dioxide nanotubes in an ultrasonic environment, so that the substrate surface will have an imprint of nanotube distribution and defects and cracks are eliminated; then the second step of anodization is carried out on this basis, so that the pore size of the grown titanium dioxide nanotubes is more uniform and the arrangement is more orderly.
[0015] When preparing CoMo-TNA in step (3), the following steps are included: first, preparing a Co-Mo oxide layer deposition solution, and the preparation method is as follows: CoSO4·7H2O, Na3C6H5O7·2H2O and Na2MoO4·2H2O are mixed at a molar concentration ratio of 0.1-0.2:0.2-0.3:0.005-0.01, and the pH value of the system solution is adjusted to 8-10 to obtain a Co-Mo oxide layer deposition solution; then, the Co-Mo oxide layer deposition solution is deposited on the surface of TNA by a direct current deposition method. More specifically, a Pt sheet electrode is used as an anode and TNA is used as a cathode. At a current density of 20-40 mA / cm 2 Under the following conditions, TNA is placed in a Co-Mo oxide layer deposition solution, the deposition temperature is controlled to be 40-60°C, the stirring rate is 200-400r / min, and the electrodeposition time is 3000-4000s to obtain CoMo-TNA (amorphous). After being washed with ultrapure water and dried, it is annealed in a tube furnace at 400-500°C for 1-3h to obtain CoMo-TNA (anatase).
[0016] When preparing the CoMo-BTNT anode in step (4), CoMo-TNA (anatase) is used as the cathode and Pt sheet is used as the anode. At a current density of 3-10 mA / cm 2 The cathode is immersed in a 5-15% (v%) formic acid solution and reduced for 5-10 minutes. After the reduction, the Ti in some TiO2 4+ Become Ti 3+ , the color will turn blue, and the CoMo-BTNT anode will be obtained.
[0017] Secondly, the present invention also provides a CoMo-BTNT anode, which is prepared by the above preparation method.
[0018] Thirdly, the present invention also provides an application of a CoMo-BTNT anode, which is mainly used in the degradation of antibiotics in water; specifically, the degradation method of antibiotics is:
[0019] (1) preparing a reaction solution: mixing a test solution with sodium sulfate and peroxymonosulfate, and adjusting the temperature of the solution system to maintain at 20-30° C. to obtain a reaction solution, placing a CoMo-BTNT anode in the reaction solution and reacting for a period of time under power-on;
[0020] (2) After filtering the reaction solution, measure the UV-visible absorbance of the reaction solution, and substitute the measured absorbance data into the linear equation of absorbance and antibiotic concentration to obtain the antibiotic concentration in the test solution.
[0021] The technical solution of the embodiment of the present invention has at least the following advantages and beneficial effects:
[0022] 1. The present invention successfully synthesized CoMo-BTNT anode material and established a method for degrading antibiotics in wastewater based on CoMo-BTNT anode material. The method mainly utilizes CoMo-BTNT anode material in combination with peroxymonosulfate (PMS) and degrades the antibiotics in the power-on state. The degradation method can degrade antibiotics in water quickly, with high precision and high sensitivity, and shows good application performance in actual water samples.
[0023] 2. The present invention uses TNA as a base layer and deposits an active CoMo oxide layer thereon to prepare CoMo-BTNT, wherein the synergistic effect of Co and Mo is conducive to the formation of oxygen vacancies in the main lattice and the redox pairs of Co and Mo species, thereby improving the conductivity and oxidation capacity of the anode; in addition, redox pairs (CoII / CoIII and MoIV / MoVI) are formed between Co and Mo, which promotes the redox cycle of Co species, thereby improving the oxidation capacity of the catalyst; based on this, the present invention develops a CoMo-BTNT anode with synergistic catalysis of Co and Mo, improves the conductivity and electrocatalytic performance of the anode, constructs an effective electrically assisted activation PMS system for tetracycline degradation, and provides a new solution for the treatment of tetracycline wastewater.
[0024] 3. The CoMo-BTNT of the present invention can effectively activate PMS, so that PMS is activated to generate sulfate radicals (SO4 ·- ), superoxide anion (O2 ·- ) and singlet oxygen radicals ( 1 O2) and other active oxygen species, SO4 ·- The higher redox potential and longer half-life of SO4 enable it to effectively contact and oxidize target pollutants and function over a wider pH range. ·- It has higher selectivity and can directly attack specific electron-rich functional groups such as amino (-NH2), hydroxyl (-OH) and other organic compounds containing unsaturated bonds through electron transfer reactions. 1 O2 has a longer lifetime and wider pH tolerance, and due to its unoccupied π* orbital, it shows high electrophilicity and selectivity for electron-rich species. ·- and 1 O2 can quickly and effectively oxidize high-priority pollutants with little interference from the actual wastewater matrix, which lays the foundation for the selective detection and degradation of antibiotic pollutants in the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the preparation process of CoMo-BTNT in Example 1 of the present invention;
[0026] Figure 2 The SEM images of CoMo-BTNT prepared in Example 1 of the present invention and BTNT prepared in Comparative Example 1 are shown; wherein, Figure 2 (a) and Figure 2 (c) Top view and side view of BTNT, respectively; Figure 2 (b) and Figure 2 (d) Top view and side view of CoMo-BTNT, respectively; Figure 2 (e)- Figure 2 (h) is the EDS element mapping of CoMo-BTNT;
[0027] Figure 3 X-ray diffraction patterns of TNA (anatase), Co / Mo-TNA (amorphous) prepared in Example 1 of the present invention, CoMo-TNA (anatase) and CoMo-BTNT;
[0028] Figure 4 The results of tetracycline degradation within 60 minutes under different experimental groups are shown in the figure;
[0029] Figure 5 The graph is the result of the degradation effect of tetracycline at different current densities;
[0030] Figure 6 This is the result diagram of the degradation effect of tetracycline at different PMS dosages;
[0031] Figure 7 The figure is the result of the degradation effect of tetracycline at different pH values;
[0032] Figure 8 This is a graph showing the stability results of the CoMo-BTNT anode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] The following is a detailed description of a CoMo-BTNT anode, a preparation method and an application thereof provided in an embodiment of the present invention.
[0035] A method for preparing a CoMo-BTNT anode comprises the following steps:
[0036] (1) Preparation of Ti substrate: First, the titanium foil is polished with sandpaper of 600, 800, 1500 and 2000 meshes in sequence to remove the oxide layer on the surface of the titanium foil, and then the titanium foil is cut into titanium sheets of the required size. Thereafter, the titanium sheet is cleaned in an ultrasonic bath with acetone, ethanol and ultrapure water in sequence for 30-60 min, and the cleaned titanium sheet is immersed in an oxalic acid solution with a concentration of 10-20%, and heated in a water bath at a constant temperature of 90-100° C. for 1.5-2.5 h. When the surface of the titanium sheet becomes pockmarked, the treatment is stopped, and the sheet is cleaned to obtain a Ti substrate;
[0037] (2) Preparation of titanium dioxide nanotube array (TNA) using a Ti substrate: The Ti substrate is used as an anode and the Pt sheet is used as a cathode, and the first anodization is carried out in an electrolyte containing fluoride ions for a period of time; then, the second anodization is continued in the electrolyte containing fluoride ions for a period of time, and finally, the electrolyte remaining on the surface of the Ti substrate is rinsed off to obtain a titanium dioxide nanotube array; more specifically, the Ti substrate is used as an anode and the Pt sheet is used as a cathode in a mixed solution of 0.25% by mass NH4F and 2% by mass H2O ethylene glycol at 60V, and anodized for 1-2h; then, the anodization is continued in a mixed solution of 0.1% by mass NH4F and 1% by mass H2O ethylene glycol for 3-5h. After the oxidation is completed, the electrolyte remaining on the surface of the Ti substrate is rinsed off with ultrapure water to obtain a TNA substrate;
[0038] The first step of anodization of the present invention is to prepare a titanium dioxide nanotube array with vertical surface growth on a Ti substrate, and then use deionized water or acid to wash away the prepared titanium dioxide nanotubes in an ultrasonic environment, so that the substrate surface will have an imprint of nanotube distribution and defects and cracks are eliminated; then the second step of anodization is carried out on this basis, so that the pore size of the grown titanium dioxide nanotubes is more uniform and the arrangement is more orderly.
[0039] (3) Depositing the Co-Mo oxide layer deposition liquid onto the surface of TNA by direct current electrodeposition to prepare CoMo-TNA: First, prepare the Co-Mo oxide layer deposition liquid, and the preparation method is as follows: mix CoSO4·7H2O, Na3C6H5O7·2H2O and Na2MoO4·2H2O in a molar concentration ratio of 0.1-0.2:0.2-0.3:0.005-0.01, and adjust the pH value of the system solution to 8-10 to obtain the Co-Mo oxide layer deposition liquid; then, deposit the Co-Mo oxide layer deposition liquid onto the surface of TNA by direct current electrodeposition. More specifically, use a Pt sheet electrode as an anode and TNA as a cathode. At a current density of 20-40 mA / cm 2Under the conditions of controlling the deposition temperature to be 40-60°C and the stirring rate to be 200-400r / min, the TNA is placed in a Co-Mo oxide layer deposition solution, and the electrodeposition is performed for 3000-4000s to obtain CoMo-TNA (amorphous), which is then washed with ultrapure water and dried, and then annealed in a tube furnace at 400-500°C for 1-3h to obtain CoMo-TNA (anatase);
[0040] (4) CoMo-TNA was used as cathode and Pt sheet as anode to prepare CoMo-BTNT anode; BTNT represents blue titanium dioxide nanotube array; more specifically: CoMo-TNA (anatase) was used as cathode and Pt sheet as anode at a current density of 3-10 mA / cm 2 The cathode is immersed in a 5-15% by volume formic acid solution and reduced for 5-10 minutes. After reduction, the Ti in some TiO2 4+ Become Ti 3+ , the color will turn blue, and the CoMo-BTNT anode will be obtained.
[0041] The present invention also provides a CoMo-BTNT anode, which is prepared by the above preparation method.
[0042] The present invention also provides an application of a CoMo-BTNT anode, which is mainly manifested in the application in the degradation of antibiotics in water; the present invention is described in detail with the degradation of tetracycline antibiotics (TCs), and specifically, the degradation method of tetracycline antibiotics is:
[0043] (1) preparing a reaction solution: preparing a 60 mL solution system containing 0.03-0.08 M sodium sulfate and 0.5 mM-1.0 mM peroxymonosulfate (PMS) with the test solution, and adjusting the temperature of the solution system to maintain at 20-30° C. to obtain a reaction solution, placing CoMo-BTNT in the reaction solution and reacting for a period of time under power-on;
[0044] The initial pH value of the reaction solution is 3-4, preferably 3.83; the current density when powered is 2.5 mA / cm 2 ~5mA / cm 2 , preferably 5 mA / cm 2 .
[0045] (2) Then, 1 mL of the reaction solution was drawn into a syringe equipped with a 0.22 μm polyethersulfone syringe filter, the reaction solution was filtered, and UV-Vis spectrum analysis was performed at 357 nm by an ultraviolet spectrophotometer to measure the ultraviolet-visible absorbance of the reaction solution. The measured absorbance data was substituted into the linear equation of absorbance and antibiotic concentration to obtain the concentration of tetracycline antibiotics in the test solution; wherein the linear equation is: y=0.02672x+0.01461(R 2 =0.9993); where x represents the concentration of tetracycline antibiotics and y represents the absorbance at 357 nm (A 357 ).
[0046] To solve the problems of anatase TNA in applications, the inventors found that uniformly filling nanoparticles in the TNA channel is an effective method to significantly improve the efficiency of directional electron transfer and the active surface. Transition molybdates exhibit high electrochemical performance due to their modulated conductivity, large surface area and highly active oxidation states, and they have multiple oxidation states, low cost and environmental friendliness, which is conducive to improving redox activity.
[0047] CoMo-BTNT can effectively activate PMS, so that PMS is activated to generate sulfate radicals (SO4 ·- ), superoxide anion (O2 ·- ) and singlet oxygen radicals ( 1 O2) and other active oxygen species, SO4 ·- The higher redox potential and longer half-life of SO4 enable it to effectively contact and oxidize target pollutants and function over a wider pH range. ·- It has higher selectivity and can directly attack specific electron-rich functional groups such as amino (-NH2), hydroxyl (-OH) and other organic compounds containing unsaturated bonds through electron transfer reactions. 1 O2 has a longer lifetime and wider pH tolerance, and due to its unoccupied π* orbital, it shows high electrophilicity and selectivity for electron-rich species. ·- and 1 O2 can quickly and effectively oxidize high-priority pollutants with little interference from the actual wastewater matrix, which lays the foundation for the selective detection and degradation of antibiotic pollutants in the environment.
[0048] In addition, the synergistic effect of Co and Mo is conducive to the formation of oxygen vacancies in the main lattice, Co and Mo species redox pairs, thereby improving the conductivity and oxidation capacity of the anode. In addition, redox pairs (CoII / CoIII and MoIV / MoVI) are formed between Co and Mo, which promotes the redox cycle of Co species, thereby improving the oxidation capacity of the catalyst. Based on this, the present invention develops a CoMo-BTNT anode catalyzed by Co and Mo, improves the conductivity of the anode, constructs an effective electrically assisted activation PMS degradation TC system, and provides a new solution for the treatment of tetracycline wastewater.
[0049] Example 1
[0050] This embodiment provides a method for preparing a CoMo-BTNT anode, comprising the following steps:
[0051] (1) Pretreatment: The titanium foil was polished with sandpaper of 600, 800, 1500, and 2000 meshes in sequence to remove the oxide layer on the surface of the titanium foil, and then cut into 20 mm × 10 mm titanium sheets; then, acetone, ethanol, and ultrapure water were used to clean the titanium sheets in an ultrasonic bath for 30 min in sequence; the cleaned titanium sheets were immersed in a 10% oxalic acid solution and heated in a water bath at a constant temperature of 98°C for 2 h. When the surface of the titanium sheet was pockmarked, the titanium sheet was taken out and cleaned with ultrapure water to obtain a Ti substrate;
[0052] (2) Preparation of amorphous TNA:
[0053] The first step is anodization: the Ti substrate is used as the anode and the Pt sheet is used as the cathode, and anodization is performed in an ethylene glycol solution with a mass fraction of 0.25% NH4F and 2% H2O at 60V for 1h;
[0054] The second step is anodization: anodization is then performed in an ethylene glycol solution with a mass fraction of 0.1% NH4F and 1% H2O for 4 hours; after the oxidation is completed, the electrolyte remaining on the surface of the Ti substrate is rinsed with ultrapure water to obtain a TNA substrate;
[0055] (3) Preparation of CoMo-TNA: First, a Co-Mo oxide layer deposition solution was prepared: 0.14 M CoSO4·7H2O, 0.2 M Na3C6H5O7·2H2O and 0.007 M Na2MoO4·2H2O were mixed, and the pH value of the system solution was adjusted to 9 to obtain a Co-Mo oxide layer deposition solution; then, a Pt sheet electrode was used as the anode and a TNA substrate was used as the cathode. The deposition temperature was 50 °C and the current density was 30 mA / cm 2Under the conditions of , TNA was placed in a Co-Mo oxide layer deposition liquid, the deposition temperature was controlled to be 50°C, the stirring rate was 300r / min, and the electrodeposition time was 3600s, so that CoMo-TNA (amorphous) was obtained. Then, it was washed with ultrapure water and dried, and annealed at 450°C in a tube furnace for 2h to obtain CoMo-TNA (anatase).
[0056] (4) Preparation of CoMo-BTNT anode: CoMo-TNA (anatase) was used as cathode and Pt sheet as anode. The current density was 5 mA / cm 2 Under the conditions, the cathode was immersed in a 10% by volume formic acid solution and reduced for 5 minutes to obtain a CoMo-BTNT anode. The specific preparation process is shown in the schematic diagram. Figure 1 .
[0057] The prepared CoMo-BTNT anode was used to degrade tetracycline antibiotics in water samples. The degradation method was as follows: (1) preparing a reaction solution: the test solution was mixed with 0.05 M sodium sulfate and 1.0 mM peroxymonosulfate to form a 60 mL solution system, and the temperature of the solution system was adjusted to room temperature to obtain a reaction solution. The prepared CoMo-BTNT anode was placed in the reaction solution and heated at a current density of 5 mA / cm 2 React for 10 minutes under the power-on state;
[0058] (2) 1 mL of the reaction solution was drawn into a syringe equipped with a 0.22 μm polyethersulfone syringe filter, the reaction solution was filtered, and UV-Vis spectrum analysis was performed at 357 nm by an ultraviolet spectrophotometer to measure the ultraviolet-visible absorbance of the reaction solution, and the measured absorbance data was substituted into the linear equation of absorbance and antibiotic concentration to obtain the concentration of tetracycline antibiotics in the test solution; wherein the linear equation is: y=0.02672x+0.01461(R 2 =0.9993); wherein x represents the concentration of tetracycline antibiotics and y represents the absorbance at 357 nm.
[0059] Example 2
[0060] The difference between Example 2 and Example 1 is that in step (3), the molar concentration ratio of CoSO4·7H2O, Na3C6H5O7·2H2O and Na2MoO4·2H2O is 0.15:0.25:0.006.
[0061] Example 3
[0062] The difference between Example 3 and Example 1 is that in step (3), annealing is performed at 400° C. for 2 h.
[0063] Example 4
[0064] The difference between Example 4 and Example 1 is that: in step (4), at a current density of 6 mA / cm 2 The cathode was immersed in a 15% by volume formic acid solution and reduced for 10 minutes.
[0065] Comparative Example 1
[0066] The difference between this comparative example and Example 1 is that the electrodeposition step (3) is not included; that is, the Ti substrate is directly annealed after two-step anodization and then cathode reduction, and the final product is recorded as BTNT.
[0067] Comparative Example 2
[0068] The difference between this comparative example and Example 1 is that: the electrodeposition step of step (3) is not included and step (4) is not included; that is, after the Ti substrate is anodized in two steps, it is annealed at 450° C. for 1 h, and the final product is recorded as TNA (anatase).
[0069] It should be noted that, in the following experimental examples, unless otherwise specified, the CoMo-BTNT used is prepared by the preparation method of Example 1. In addition, Co / Mo-BTNT and CoMo-BTNT mentioned herein and in the drawings of the specification are synonymous.
[0070] Experimental Example 1
[0071] 1. The morphology of the Co / Mo-BTNT prepared in Example 1 and the BTNT material prepared in the comparative example was characterized and analyzed by field emission scanning electron microscopy (SEM); Figure 2 (a)-(c); among which, Figure 2 (a) and Figure 2 (c) shows the top view and side view of BTNT, respectively. Figure 2 (a) and Figure 2 (c) It can be observed that a uniform and dense tubular structure is formed vertically on the titanium foil. The average length of the nanotube array is 8.41 μm, the outer diameter is 136 nm, and the wall thickness is about 22 nm. Figure 2 (b) and Figure 2 (d) shows the top view and side view of CoMo-BTNT, respectively. Figure 2 (b) and Figure 2 (d) It can be observed that a uniform CoMo oxide layer with a thickness of about 2.39 μm is deposited on the top of the CoMo-BTNT, and a TiO2 nanotube middle layer with a length of 5.20 μm is formed after anodization in the middle. Due to the coverage of the CoMo oxide layer, the diameter of the TiO2 nanotube middle layer cannot be measured.
[0072] also, Figure 2 (e)- Figure 2 (h) is the EDS element mapping diagram of CoMo-BTNT, which clearly shows that the three elements Co, Mo, Ti, and O are evenly distributed on the surface of the CoMo-BTNT anode; the above results show that Example 1 of the present invention successfully synthesized the CoMo-BTNT anode material.
[0073] 2. The crystal structures of TNA (anatase), CoMo-TNA (amorphous), CoMo-TNA (anatase) and CoMo-BTNT were determined by X-ray powder diffraction (XRD). Figure 3 shown by Figure 3 It can be seen that the characteristic diffraction peaks of the TNA (anatase) sample are 25.1°, 37.8°, 47.9°, 53.8°, 54.9°, 70.5° and 76.2°, respectively, corresponding to the (101), (004), (200), (105), (211), (220) and (301) crystal planes of the TiO2 anatase phase, which are basically consistent with the standard card (PDF#21-1272), proving the successful synthesis of TNA (anatase); and after DC electrodeposition and annealing calcination, CoMo -TNA (amorphous) and CoMo-TNA (anatase) The diffraction peaks of the anatase phase are weakened, which may be due to the deposition of the CoMo oxide layer on the top of TNA; a series of diffraction peaks appear in the range of 40° to 50°, corresponding to the (200) crystal plane of Co3Mo, proving the successful introduction of the CoMo oxide layer; compared with CoMo-TNA (anatase), new diffraction peaks belonging to MoO3 and CoMoO4 appear in CoMo-BTNT after cathode reduction, proving the successful preparation of CoMo-BTNT.
[0074] Experimental Example 2
[0075] In order to demonstrate the electrocatalytic degradation performance of CoMo-BTNT on tetracycline, the degradation method of the present invention was used to add the following experimental group systems to multiple identical test solutions to perform degradation experiments on tetracycline: CoMo-BTNT, E, PMS, PMS+E, CoMo-BTNT+E, CoMo-BTNT+PMS and CoMo-BTNT+PMS+E, where E represents power on; the degradation efficiency of tetracycline within 60 min under different experimental group systems is shown in Figure 4 .
[0076] Depend on Figure 4 It can be seen that: ① When CoMo-BTNT is used alone, the removal rate of TC is 2.12%, which can be ignored; this indicates that when only CoMo-BTNT is used, the adsorption effect on tetracycline is weak, and no additional adsorption experiment is required before removal.
[0077] ② In the system with only power supply (E), only 20.07% of TC was removed, which is because the electrochemical oxidation is not effective in removing pollutants.
[0078] ③When only PMS was used, the removal efficiency of TC reached 22.67%, because PMS hydrolysis can produce SO4 ·- , OH, O2 ·- , 1 O2 and other active substances.
[0079] ④When CoMo-BTNT was added under power-on condition, the removal efficiency of TC increased to 44.46%, indicating that the introduction of electrochemistry can improve the catalytic degradation effect of CoMo-BTNT on tetracycline.
[0080] ⑤ In order to compare the activation behavior of PMS in the E+PMS system, under the same experimental conditions, the original Ti electrode was used as the anode to degrade TC, and the removal efficiency reached 41.82% within 60 min, which was attributed to the fact that the current can promote the activation of ·OH and SO4 ·- The production of OH and SO4 ·- Can be converted into each other.
[0081] ⑥ Compared with the PMS system alone, the removal efficiency of TC by the CoMo-BTNT+PMS system reached 63.59%, indicating that the prepared CoMo-BTNT can significantly activate PMS to produce active free radicals.
[0082] ⑦ In the E+CoMo-BTNT+PMS system, the removal efficiency of TC reached 91.63%, indicating that Co 2+ and Mo 6+ Can be converted into Co 3+ and Mo 5+ , so that PMS is activated to form more active free radicals. Therefore, CoMo-BTNT and PMS have obvious synergistic and reinforcing effects under the power-on state, and are optimal for the electrocatalytic degradation of tetracycline.
[0083] Experimental Example 3
[0084] This experimental example is to explore the effects of different current density, PMS dosage, initial pH value and other factors on the electrocatalytic degradation performance of CoMo-BTNT;
[0085] 3.1 Current density
[0086] When other experimental conditions were the same, different current densities were applied to evaluate the degradation effect of E+CoMo-BTNT+PMS system on TC. The results are shown in Figure 5 As shown by Figure 5It can be seen that:
[0087] When the current density is increased from 2.5 mA / cm 2 Increase to 5mA / cm 2 When the current density continued to increase, the degradation efficiency of TC did not increase significantly. It is speculated that this may be because too high a current density will intensify the side reaction at the anode, and the side reaction at the anode will produce O2, which will react with HSO5 - Competing for electrons, resulting in SO4 ·- The production of is reduced, generating a weaker redox potential 1 O2, so that the E+CoMo-BTNT+PMS system has no significant improvement in the degradation efficiency of TC. Considering all factors, the current density of 5 mA / cm 2 As the optimal current density for subsequent reactions.
[0088] 3.2 PMS dosage
[0089] Effect of PMS dosage on the catalytic degradation of tetracycline Figure 6 As shown. Figure 6 The results show that in the E+CoMo-BTNT+PMS system, an important factor in the degradation of tetracycline is the PMS dosage. Within 60 minutes, when the PMS dosage increased from 0.5mM to 1.0mM, the removal efficiency of tetracycline increased from 63.14% to 86.13%. However, as the PMS dosage continued to increase, the removal effect of tetracycline did not improve significantly, and even showed a slight downward trend. This may be because excessive PMS has a strong effect on SO4 ·- It has a certain removal effect on ·OH.
[0090] 3.3 Initial pH
[0091] Based on SO4 ·- One of the most important factors in advanced oxidation treatment (AOP) is pH value, especially AOP combined with electrochemistry. This paper conducted experiments in the range of initial pH value of 3-11 to explore the effect of different initial pH values on the degradation of tetracycline by E+CoMo-BTNT+PMS system. The results are as follows: Figure 7 As shown by Figure 7It can be seen that within 60 minutes, when the initial pH value of the system solution was 11 and the initial pH value (i.e., the unadjusted pH value) was 3.85, the removal efficiency of tetracycline was equivalent, although the removal efficiency when the initial pH value of the system solution was 11 was slightly higher (88.68%) than the removal efficiency of the initial solution system without adjusting the pH value, because some PMS was alkaline activated. When the initial pH values were 3, 5, 7, and 9, respectively, the degradation rate of tetracycline by the E+CoMo-BTNT+PMS system decreased, which were 70.07%, 83.98%, 84.31%, and 79%, respectively. This is because the overacid solution will accelerate the HSO5 - The protonation of PMS was higher in neutral and alkaline solutions, while PMS self-decomposed faster in neutral and alkaline solutions. Finally, considering the simplicity of operation, the initial pH value of 3.85 (unadjusted pH value) was still selected for the degradation of tetracycline.
[0092] Experimental Example 4
[0093] This experimental example is to explore the stability of CoMo-BTNT, as follows:
[0094] The CoMo-BTNT anode material prepared in Example 1 was subjected to a cycle test under the same operation to explore the stability of the CoMo-BTNT anode in removing TC. The results are shown in FIG. Figure 8 ;
[0095] The operation steps and reaction conditions of the cycle test are as follows:
[0096] 1. Material regeneration: After each cycle reaction, the CoMo-BTNT was rinsed with ultrapure water, air-dried, and annealed at 450℃ for 1h. After annealing, the CoMo-BTNT was used as the cathode and the Pt sheet was used as the anode at 5mA / cm 2 The cathode was reduced for 5 min, rinsed with ultrapure water, and dried naturally to obtain the regenerated CoMo-BTNT.
[0097] 2. Cycle experiment:
[0098] 1) At a current density of 5 mA / cm 2 ; Initial tetracycline concentration = 30 mg / L; Sodium sulfate concentration
[0099] =60mmol / L; PMS dosage = 1mmol / L; temperature is room temperature; the experiment was carried out under the condition of pH value of 3.85, and CoMo-BTNT was placed in the reaction solution and reacted for a period of time (0min, 180min, 360min, 540min, 720min, 900min) under the power-on state;
[0100] 2) At 0 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min and 45 min, 1 mL of the reaction solution was drawn from the sampling port with a syringe, filtered with a 0.22 μm polyethersulfone filter and then placed in a quartz cuvette, and its absorbance at 357 nm was detected by an ultraviolet spectrophotometer; after tetracycline was degraded, the absorbance at 357 nm and the tetracycline concentration showed a good linear relationship in the concentration range of 0 to 45 mg / L, and the linear regression equation established between the concentration of the standard solution and the absorbance was: y=0.02672x+0.01461, wherein x represented the tetracycline concentration, and y represented the absorbance data at 357 nm, and the concentration of tetracycline in the reaction solution was calculated according to the established linear regression equation.
[0101] Depend on Figure 8 It can be seen that: after 5 cycles, the degradation efficiency of CoMo-BTNT for tetracycline was slightly reduced, but it was only reduced by 11.74%. The reduction in degradation effect may be due to the gradual occupation of active sites on the catalyst surface; and the degradation efficiency can still be achieved after 5 cycles, that is, it still maintains a high degradation efficiency. It can be seen that CoMo-BTNT has good stability.
Claims
1. A method for preparing a CoMo-BTNT anode, characterized in that: The following steps are involved: (1) preparing a Ti substrate; (2) Preparation of titanium dioxide nanotube arrays using Ti substrate; (3) depositing a Co-Mo oxide layer deposition liquid onto the surface of a titanium dioxide nanotube array by a direct current electrodeposition method, and then performing an annealing heat treatment to prepare CoMo-TNA; (4) CoMo-BTNT anode was prepared using CoMo-TNA as cathode and Pt sheet as anode.
2. The method for preparing the CoMo-BTNT anode according to claim 1, characterized in that: When preparing the Ti substrate in step (1), the following steps are included: first, removing the oxide layer on the surface of the titanium foil, then cutting it into titanium sheets of the required size, then ultrasonically cleaning the titanium sheets, and sequentially subjecting the cleaned titanium sheets to acid treatment and heat treatment. When the surface of the titanium sheets becomes rough, the treatment is stopped, and the sheets are cleaned to obtain the Ti substrate.
3. The method for preparing the CoMo-BTNT anode according to claim 1, characterized in that: When preparing the titanium dioxide nanotube array in step (2), the following steps are included: using the Ti substrate as the anode and the Pt sheet as the cathode, performing a first anodization in an electrolyte containing fluorine ions for a period of time; then continuing to perform a second anodization in the electrolyte containing fluorine ions for a period of time, and finally flushing the electrolyte remaining on the surface of the Ti substrate to obtain the titanium dioxide nanotube array.
4. The method for preparing the CoMo-BTNT anode according to claim 1, characterized in that: When preparing CoMo-TNA in step (3), the following steps are included: (3.1) preparing a Co-Mo oxide layer deposition solution: after mixing CoSO4·7H2O, Na3C6H5O7·2H2O and Na2MoO4·2H2O, adjusting the pH value of the system solution to 8-10, a Co-Mo oxide layer deposition solution is obtained; (3.2) The Co-Mo oxide layer deposition liquid is deposited onto the surface of the titanium dioxide nanotube array by a direct current electrodeposition method, and then an annealing heat treatment is performed to obtain CoMo-TNA.
5. The method for preparing the CoMo-BTNT anode according to claim 4, characterized in that: In step (3.2), a Pt sheet electrode is used as the anode and a titanium dioxide nanotube array is used as the cathode. 2 Under the following conditions, the titanium dioxide nanotube array is placed in a Co-Mo oxide layer deposition solution, and the deposition temperature and time are controlled; then the CoMo-TNA is dried and annealed for a period of time to obtain the CoMo-TNA.
6. The method for preparing the CoMo-BTNT anode according to claim 5, characterized in that: The deposition temperature is 40-60° C., and the deposition time is 3000-4000 s; during the annealing heat treatment, annealing is performed at 400-500° C. for 1-3 h.
7. The method for preparing a CoMo-BTNT anode according to claim 1, characterized in that: When preparing the CoMo-BTNT anode in step (4), CoMo-TNA is used as the cathode and Pt sheet is used as the anode. At a current density of 3-10 mA / cm 2 Under the above conditions, the cathode is immersed in a formic acid solution and reduced for a period of time to obtain a CoMo-BTNT anode.
8. A CoMo-BTNT anode, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a CoMo-BTNT anode, characterized in that: The CoMo-BTNT anode prepared by the preparation method according to any one of claims 1 to 7 is used for the degradation of antibiotics in water.
10. The use of the CoMo-BTNT anode according to claim 9, characterized in that: The degradation method of the antibiotic is: (1) preparing a reaction solution: mixing a test solution with sodium sulfate and peroxymonosulfate to obtain a reaction solution, placing a CoMo-BTNT anode in the reaction solution and reacting for a period of time under power-on conditions; (2) Then, after filtering the reaction solution, the UV-visible absorbance of the reaction solution is measured, and the measured absorbance data is substituted into the linear equation of absorbance and antibiotic concentration to obtain the antibiotic concentration in the test solution.
Citation Information
Patent Citations
Tin-molybdenum codoped titanium dioxide nanotube array electrode and preparation method
CN106917128A
Preparation method of NiMo alloy catalyst supported by TiO2 nanotube array
CN111250102A
Preparation method of Blue-TiO2 / CNT-PbO2 electrode material doped with carbon nanotubes
CN112429813A
Cited By
Anode material for electrocatalytic degradation of tetracycline as well as preparation method and application of anode material
CN120841653A